Answer:
The solved given fractional expression is [tex]\frac{17}{3}[/tex]
Therefore the given fractional expression becomes
[tex]\frac{6}{2}+\frac{8}{3}=\frac{17}{3}[/tex]
Step-by-step explanation:
Given fractional expression is [tex]\frac{6}{2}+\frac{8}{3}[/tex]
To solve the given fractional expression as below :
[tex]\frac{6}{2}+\frac{8}{3}[/tex]
[tex]=3+\frac{8}{3}[/tex]
[tex]=\frac{3\times 3+8}{3}[/tex]
( here taking the term 3 as LCM )
[tex]=\frac{9+8}{3}[/tex] ( by adding the sums here )
[tex]=\frac{17}{3}[/tex]
[tex]\frac{6}{2}+\frac{8}{3}=\frac{17}{3}[/tex]
Therefore the solved given fractional expression is [tex]\frac{17}{3}[/tex]
Therefore the given fractional expression becomes
[tex]\frac{6}{2}+\frac{8}{3}=\frac{17}{3}[/tex]
The solved given fractional expression is [tex]\frac{6}{2}+\frac{8}{3}=\frac{17}{3}[/tex]